Identification of microstructured materials by phase and group velocities - Janno, Jaan; Engelbrecht, Jüri (Mathematical Modelling and Analysis, 2009)
An inverse problem to determine parameters of microstructured solids by means of group and phase velocities of wave packets is studied. It is proved that in the case of normal dispersion the physical solution is unique and in the case of anomalous dispersion two physical solutions occur. Numerical tests are presented.First published online: 14 Oct 2010